ANALISIS KEMAMPUAN MENULIS KARANGAN NARASI PADA SISWA KELAS IV SEKOLAH DASAR : (Penelitian Deskriptif Kualitatif pada Siswa Kelas IV Salah Satu Sekolah Dasar di Kecamatan Purwakarta Kabupaten Purwakarta) - Eliza Rahayu, - (2023)
Menulis merupakan proses kreatif yang dilakukan dengan menggunakan bahasa tulis untuk menyampaikan informasi dari penulis kepada pembaca. Karangan narasi adalah suatu wacana atau karangan yang bertujuan untuk mengisahkan atau menceritakan suatu peristiwa atau kejadian dari waktu ke waktu. Kemampuan ini menjadi kemampuan yang penting karena merupakan suatu kemampuan seseorang dalam memahami hasil tulisanya sendiri. Tujuan penelitian ini adalah untuk mengetahui kemampuan menulis karangan narasi siswa kelas IV, untuk mengetahui kesulitan siswa dalam mengembangkan kemampuan menulis karangan narasi siswa kelas IV, untuk mendeskripsikan solusi untuk mengatasi kesulitan menulis karangan narasi pada siswa kelas IV. Penelitian ini menggunakan deskriptif kualitatif dengan subjek penelitian 22 siswa kelas IV. Teknik pengambilan data yang digunakan dalam penelitian ini adalah pedoman studi dokumentasi dan pedoman wawancara. Hasil penelitian menunjukkan bahwa siswa kelas IV memiliki kemampuan yang berbeda antara siswa satu dengan yang lainnya. Berdasarkan aspek yang terdapat dalam menulis karangan narasi kemampuan siswa paling tinggi terlihat pada aspek latar dan isi gagasan. Aspek alur, organisasi isi, pilihan kata atau diksi dan struktur teks narasi merupakan aspek cukup. Sementara aspek tokoh serta ejaan dan tanda baca merupakan aspek terendah siswa dalam menulis karangan narasi. Faktor kesulitan siswa yaitu kurangnya motivasi dan pemahaman siswa dalam menulis karangan narasi serta pembelajaran yang kurang menarik. Solusi yang diterapkan untuk mengatasi kesulitan menulis karangan narasi yaitu dengan memberi motivasi tentang pentingnya menulis karangan narasi dan mengajak siswa berlatih menulis karangan narasi dengan baik dan benar serta menggunakan bahan ajar yang telah dibuat dengan kreatif bagi siswa agar menarik perhatian siswa untuk bisa menerima materi pembelajaran dengan baik. ----- Writing is a creative process that uses written language to convey information from the writer to the reader. A narrative essay is a discourse or essay that aims to tell or narrate an event or events from time to time. This ability is important because it is a person's ability to understand the results of his writing. The purpose of this study was to determine the ability to write narrative essays in class IV students, to find out the difficulties of students in developing the ability to write narrative essays in class IV students, and to describe solutions to overcome difficulties in writing narrative essays in class IV students. This study used descriptive qualitative research subjects, 22 students of class IV. The data collection techniques used in this study were documentation study guidelines and interview guidelines. The study results showed that fourth-grade students had different abilities from one student to another. Based on the aspects of writing narrative essays, the highest student ability can be seen in the background aspect and the content of the idea. Aspects of plot, content organization, choice of words or diction and narrative text structure are sufficient. At the same time, the character aspect, spelling, and punctuation are the lowest aspects of students in writing narrative essays. Factors of student difficulty, namely the need for more motivation and understanding of students in writing narrative essays and less interesting learning. The solution that is applied to overcome the difficulties of writing narrative essays is to provide motivation about the importance of writing narrative essays and invite students to practice writing narrative essays properly and correctly, and use teaching materials that have been made creatively for students to attract students' attention to be able to receive learning material well good. Writing is a creative process that uses written language to convey information from the writer to the reader. A narrative essay is a discourse or essay that aims to tell or narrate an event or events from time to time. This ability is important because it is a person's ability to understand the results of his writing. The purpose of this study was to determine the ability to write narrative essays in class IV students, to find out the difficulties of students in developing the ability to write narrative essays in class IV students, and to describe solutions to overcome difficulties in writing narrative essays in class IV students. This study used descriptive qualitative research subjects, 22 students of class IV. The data collection techniques used in this study were documentation study guidelines and interview guidelines. The study results showed that fourth-grade students had different abilities from one student to another. Based on the aspects of writing narrative essays, the highest student ability can be seen in the background aspect and the content of the idea. Aspects of plot, content organization, choice of words or diction and narrative text structure are sufficient. At the same time, the character aspect, spelling, and punctuation are the lowest aspects of students in writing narrative essays. Factors of student difficulty, namely the need for more motivation and understanding of students in writing narrative essays and less interesting learning. The solution that is applied to overcome the difficulties of writing narrative essays is to provide motivation about the importance of writing narrative essays and invite students to practice writing narrative essays properly and correctly, and use teaching materials that have been made creatively for students to attract students' attention to be able to receive learning material well good. Writing is a creative process that uses written language to convey information from the writer to the reader. A narrative essay is a discourse or essay that aims to tell or narrate an event or events from time to time. This ability is important because it is a person's ability to understand the results of his writing. The purpose of this study was to determine the ability to write narrative essays in class IV students, to find out the difficulties of students in developing the ability to write narrative essays in class IV students, and to describe solutions to overcome difficulties in writing narrative essays in class IV students. This study used descriptive qualitative research subjects, 22 students of class IV. The data collection techniques used in this study were documentation study guidelines and interview guidelines. The study results showed that fourth-grade students had different abilities from one student to another. Based on the aspects of writing narrative essays, the highest student ability can be seen in the background aspect and the content of the idea. Aspects of plot, content organization, choice of words or diction and narrative text structure are sufficient. At the same time, the character aspect, spelling, and punctuation are the lowest aspects of students in writing narrative essays. Factors of student difficulty, namely the need for more motivation and understanding of students in writing narrative essays and less interesting learning. The solution that is applied to overcome the difficulties of writing narrative essays is to provide motivation about the importance of writing narrative essays and invite students to practice writing narrative essays properly and correctly, and use teaching materials that have been made creatively for students to attract students' attention to be able to receive learning material well good.